Colleagues Rally Round for Flood Affected Colleague - Hanisah, Kasbon (Pusat Bahasa Moden (PBM), 2021)
It is not too late to wish everyone a Happy New Year in spite of the wet and windy season welcoming the start of 2021. Continuous cold and heavy rain since New Year’s Eve caused flooding in several states of the country and parts of Pahang were swamped in floodwaters. Our close associate, Encik Mohd Iszuani Bin Mohd Hassan or better known as Sensei Iszuani, from Maran suffered properties damage and loss due to the flooding on the weekend, and was later brought to a nearby relief center.